THE IMPACT OF SOLAR RADIATION RETURNING FROM THE EARTH'S SURFACE ON THE ATMOSPHERIC RADIATION FIELD (Scientific journal of the Fergana State University, 2025)
This article examines the effect of solar radiation returning from the Earth's surface on the solar radiation field in the atmosphere. A calculation method based on Lambert's law for the intensity of the outgoing radiation flow from the Earth's surface has been developed, demonstrating its impact on the diffuse and non-diffuse radiation flows in the atmosphere. The results of the calculations provide a theoretical assessment of the illumination level of solar panels by solar radiation flow and allow for the identification of optimal conditions for their stationary installation on the Earth's surface.